2014
DOI: 10.3389/fpsyg.2014.00674
|View full text |Cite
|
Sign up to set email alerts
|

Early recurrent feedback facilitates visual object recognition under challenging conditions

Abstract: Standard models of the visual object recognition pathway hold that a largely feedforward process from the retina through inferotemporal cortex leads to object identification. A subsequent feedback process originating in frontoparietal areas through reciprocal connections to striate cortex provides attentional support to salient or behaviorally-relevant features. Here, we review mounting evidence that feedback signals also originate within extrastriate regions and begin during the initial feedforward process. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
134
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(156 citation statements)
references
References 87 publications
21
134
1
Order By: Relevance
“…Further support for the behavioral relevance of this representation comes from our finding that pairwise behavioral judgments of the stimuli were more strongly correlated with the identity-based representation than with the imagebased representation, and that responses in the face-selective regions predicted behavior during temporal periods in which responses in the face-selective regions transitioned toward an identity-based representation. Given that the observed transition occurs relatively late, and that it corresponds with a secondary later peak in the classification accuracy function, it seems somewhat unlikely that it arises as a consequence of a single initial feedforward sweep (34) but instead reflects recurrent/feedback processing (19,35).…”
Section: Discussionmentioning
confidence: 99%
“…Further support for the behavioral relevance of this representation comes from our finding that pairwise behavioral judgments of the stimuli were more strongly correlated with the identity-based representation than with the imagebased representation, and that responses in the face-selective regions predicted behavior during temporal periods in which responses in the face-selective regions transitioned toward an identity-based representation. Given that the observed transition occurs relatively late, and that it corresponds with a secondary later peak in the classification accuracy function, it seems somewhat unlikely that it arises as a consequence of a single initial feedforward sweep (34) but instead reflects recurrent/feedback processing (19,35).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there is evidence that feedback signals from inferotemporal conceptual areas impact processing in the visual cortex just 100ms following stimulus onset, well before the onset of endogenous attention (Wyatte et al 2014). Similarly, Moshe Bar and colleagues have shown that conceptual 2 There are a number of other well-known modularist approaches to theory of mind (Fodor 1992;Leslie et al 2004;Scholl and Leslie 1999); however, these accounts tend not to sharply distinguish between implicit and explicit mindreading systems, as the two-systems theorists do.…”
Section: Why Two Systems?mentioning
confidence: 99%
“…Thus bottom-up perceptual input and higher order systems iteratively process information until arriving at a conscious percept and action sequence (see also Cunningham et al, 2007). The role of reentrant processing between higher order and lower order regions occurs throughout the perceptual-processing hierarchy (Wyatte, Jilk, & O'Reilly, 2014). We have created an example from the visual perceptual modality (see Figure 2), but we expect similar processing in other sensory modalities specified in the PMIR (also see Ferdenzi, Rouby, & Bensafi, this issue, on olfactory perception).…”
Section: Dynamic Processingmentioning
confidence: 99%